Rummen i biblioteksrummet : perspektiv på bibliotekslokalens anpassning - Niemi,Oscar (2024)
In this master's thesis I will study library space in its practical use in relation to the professionals working in it daily, i.e. the library staff. It seems that this profession should have a unique knowledge base around how the library is used and how space can be organised to benefit the users, the staff and the collections. The library is closely connected to and affected by society and societal changes. It is an open, public place free for everyone to visit. With national regulations in mind, it is a substantial task to accommodate a space to suit everyone's needs. The aim of this thesis is to find out how the library staff view the library space and how it functions, as well as mapping out who makes decisions and what those decisions are based upon. Interviews with library staff were conducted. Participating libraries were of different sizes, ages and geographical locations within the Swedish county of Skåne. These interviews will be related to theoretical perspectives such as the four spaces and Abbott’s System of professions. Findings show that library staff above all value the libraries’ role as a meeting place and find it important that the library space mirrors this. The staff adjusts the library space based on use, with the goal of creating a pleasant environment that contains the library’s many functions. The range of user involvement varies, but the informants notice an increased interest overall. Planning of library space is contested by multiple actors that seek to influence this process. Difficulties concerning available space comes down to balancing various functions within the library.
Keywords: Library; librarians; library space; The four spaces; meeting place; third place; system of professions